Treatment abandonment: A report from the collaborative African network for childhood cancer care and research—CANCaRe Africa - Chagaluka, George; Afungchwi, Glenn Mbah; Landman, Lisa (Pediatr Blood Cancer, 2021)
Background: ‘Treatment abandonment’ is a common and preventable cause of child hood cancer treatment failure in low- and middle-income countries (LMIC). Risk factors and effective interventions in LMIC are reported. Poverty and costs of treatment are perceived as overriding causes in sub-Saharan Africa. The objective of this study was to study potential determinants of treatment abandonment, including aspects of treatment costs in sub-Saharan Africa, to be better informed for planned future interventions. Methods: A multicentre, prospective, observational, cohort study was conducted in five hospitals in sub-Saharan Africa. Children younger than 16 years with newly diagnosed cancer treated as inpatient with curative intent were included. The occurrence of treatment abandonment and potential determinants including aspects of treatment costs were documented during the first 3 months of treatment. Results: We included 252 patients (median age 6.0, range 0.2–15.0 years, 54% male). The most common cancer was Burkitt lymphoma (63/252, 25%). Seven percent of patients (18 of 252) abandoned treatment. Two thirds (65%, 163/252) of patients had to borrow money to reach the hospital for the diagnosis and start of treatment. Treatment abandonment occurred more frequently in families who had to borrow money (16/163, 10%) versus those who did not (2/89, 2%; p = .026). Conclusions: Limiting costs for families and improved counselling may reduce treatment abandonment. Development and implementation of interventions to reduce treatment abandonment are required in sub-Saharan Africa.
Keywords: Africa; common and curable cancers; costs; Global Initiative for Childhood Cancer; survival; treatment abandonment; Festus Njuguna; Peter Hesseling; Peter Hesseling; ACE: Genetic Medicine; WAGMC; University of Ghana